2017
DOI: 10.1104/pp.16.01726
|View full text |Cite
|
Sign up to set email alerts
|

Resolvase OsGEN1 Mediates DNA Repair by Homologous Recombination

Abstract: Yen1/GEN1 are canonical Holliday junction resolvases that belong to the RAD2/XPG family. In eukaryotes, such as budding yeast, mice, worms, and humans, Yen1/GEN1 work together with Mus81-Mms4/MUS81-EME1 and Slx1-Slx4/SLX1-SLX4 in DNA repair by homologous recombination to maintain genome stability. In plants, the biological function of Yen1/GEN1 remains largely unclear. In this study, we characterized the loss of function mutants of OsGEN1 and OsSEND1, a pair of paralogs of Yen1/GEN1 in rice (Oryza sativa). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 99 publications
2
23
0
Order By: Relevance
“…The residual chiasmata in osshoc1-2 were randomly distributed, indicating that OsSHOC1 is involved in the formation of class I COs. Consistently, a further decrease in the number of COs was observed in the double mutant of OsSHOC1 and OsGEN1, the latter of which encodes a resolvase required for class II CO formation (Wang et al, 2017).…”
Section: Osshoc1-osptd Complex Is Indispensable For Rice Co Formationsupporting
confidence: 60%
See 3 more Smart Citations
“…The residual chiasmata in osshoc1-2 were randomly distributed, indicating that OsSHOC1 is involved in the formation of class I COs. Consistently, a further decrease in the number of COs was observed in the double mutant of OsSHOC1 and OsGEN1, the latter of which encodes a resolvase required for class II CO formation (Wang et al, 2017).…”
Section: Osshoc1-osptd Complex Is Indispensable For Rice Co Formationsupporting
confidence: 60%
“…The hypothesized upstream function of OsSHOC1 in rice CO formation in relation to other ZMM proteins was investigated by genetic analysis. The mean chiasma frequency in oshei10 (6.06 6 2.86, n 5 167), as determined by Wang et al (2017), was much higher than that in osshoc1-2 (3.40 6 1.89, n 5 142) or osptd-1 (3.12 6 1.76, n 5 113). Moreover, the mean chiasma frequency in osshoc1-2 oshei10 double mutants (3.36 6 1.90, n 5 94) was similar to that in osshoc1-2, osptd-1, and osshoc1-2 osptd-1 (Table 1).…”
Section: The Interdependent Loading Pattern Between Osshoc1 and Osptdmentioning
confidence: 85%
See 2 more Smart Citations
“…There are a scarce number of reports indicating the preferred DNA repair pathway (non‐homologous end joining versus homologous recombination) in uninucleate microspores. It has been shown that the cells are sensitive to mutation of OsGEN1 gene involved in homologous recombination DNA repair in rice and initiate programmed cell death during the first asymmetric mitotic division (Wang et al , ). This can potentially suggest that the HR pathway is essential for male gametogenesis and microspores possess an active DNA repair mechanism.…”
Section: Discussionmentioning
confidence: 99%